1995
DOI: 10.1016/0277-3791(95)00081-x
|View full text |Cite
|
Sign up to set email alerts
|

Dating raised bogs: New aspects of AMS 14C wiggle matching, a reservoir effect and climatic change

Abstract: -High resolution AMS dating of Holocene raised bog deposits (Engbertsdijksvenen,The Netherlands) shows natural 14C variations (wiggles) which can be matched with the dendrochronological calibration curve. Comparison of our results with other, conventionally dated peat cores and the A14C record shows an unexpected and as yet unreported reservoir effect, and a QSR marked and sudden wetting of the bog surfaces coinciding with the advent of a SpGrer-type solar minimum (the Homeric minimum). The potential of AMS da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
173
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(179 citation statements)
references
References 21 publications
5
173
0
1
Order By: Relevance
“…These RCA values have been reported fro a range of sites across northern peatlands, and rates of accumulation vary from a high of 88.6 gC/m 2 /yr (Tolonen and Turunen, 1996) to as low as 0.2 gC/m 2 /yr on Baffin Island (Schlesinger, 1990). There are recognised problems with this technique including: long-term anoxic decay in the catotelm ; reservoir effects (Kilian et al, 1995(Kilian et al, , 2000; poor estimates of peat bulk density; and short term changes in carbon accumulation will not be well represented (Hilbert et al, 2000). In order to resolve some of these issues the short-lived radioisotope 210 Pb has been used (e.g.…”
Section: Introductionmentioning
confidence: 78%
“…These RCA values have been reported fro a range of sites across northern peatlands, and rates of accumulation vary from a high of 88.6 gC/m 2 /yr (Tolonen and Turunen, 1996) to as low as 0.2 gC/m 2 /yr on Baffin Island (Schlesinger, 1990). There are recognised problems with this technique including: long-term anoxic decay in the catotelm ; reservoir effects (Kilian et al, 1995(Kilian et al, , 2000; poor estimates of peat bulk density; and short term changes in carbon accumulation will not be well represented (Hilbert et al, 2000). In order to resolve some of these issues the short-lived radioisotope 210 Pb has been used (e.g.…”
Section: Introductionmentioning
confidence: 78%
“…Indeed, Kilian et al (1995) found several published peat cores where sequences of bulk 14 C dates followed the shape of the 14 C calibration curve, but where the matches improved when a positive 14 C age offset was assumed for the peat bulk 14 C dates (see Fig. 1A-D).…”
Section: Introductionmentioning
confidence: 89%
“…These results were not expected; rootlets are generally believed to cause younger 14 C ages because they penetrate from higher, younger levels (e.g., Shore et al, 1995). Kilian et al (1995) then proceeded to see whether other peat cores could also possess unidentified 14 C reservoir effects.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations